Small-particle-size positive electrode active material, preparation method and application thereof

By doping carbon source nitrogen source composition into the positive electrode material of lithium iron phosphate battery and sintering to prepare a small-particle-size positive electrode active material, the problems of low capacity retention and poor circulation performance of existing materials under low temperature environments are solved, and the structural stability and electrochemical performance of the material are improved.

CN119503755APending Publication Date: 2025-02-25HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411684654.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing lithium iron phosphate battery positive electrode materials have low capacity retention rate and poor circulation performance in low temperature environments, which limits their application in extreme environments.

Method used

By ball milling and mixing the iron-doped carbon source nitrogen source composition, lithium hydroxide and ammonium dihydrogen phosphate, precursor particles are formed and sintered in an inert atmosphere, a small-particle-sized positive electrode active material was prepared. This method improves the structural stability and electrochemical properties of the material by uniformly distributing iron ions and forming an N-doped carbon layer.

Benefits of technology

The prepared small particle size positive electrode active material has excellent electrochemical properties, including improved capacity retention rate and improved circulation performance under low temperature environments, extending the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005149130070000071
    Figure BDA0005149130070000071
  • Figure BDA0005149130070000081
    Figure BDA0005149130070000081
Patent Text Reader

Abstract

The invention discloses a small-particle-size positive electrode active material, a preparation method and application thereof, and belongs to the technical field of lithium ion batteries, the preparation method of the small-particle-size positive electrode active material comprises the following steps: ball-milling and mixing an iron-doped carbon source and nitrogen source composition, lithium hydroxide and ammonium dihydrogen phosphate for 1-1.5 h to obtain precursor particles, the iron-doped carbon source and nitrogen source composition is prepared by complexing a gallic acid / melamine composition and ferric chloride hexahydrate; and sintering the precursor particles in an inert atmosphere to obtain the small-particle-size positive electrode active material. The small-particle-size positive electrode active material prepared by the invention can be applied to a lithium ion battery and has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a small-particle positive electrode active material, a preparation method and an application thereof. Background Art

[0002] In recent years, lithium-ion batteries, as chemical power sources with high specific capacity, have been widely used in mobile communications, laptops, camcorders, cameras, portable instruments and other fields. They are also the preferred supporting power sources for electric vehicles and space power sources that are vigorously studied by various countries, and have become the first choice for alternative energy. At present, the most studied positive electrode materials include LiCoO2, LiNiO2, LiMn2O4, LiFePO4 (lithium iron phosphate), etc. Among them, lithium iron phosphate positive electrode materials have gradually become a research hotspot due to their advantages such as high structural stability, good safety performance, moderate operating voltage, good platform characteristics, and large theoretical capacity.

[0003] With the development of science and technology, the requirements for battery performance are also increasing, especially in low temperature performance and ultra-long cycle stability. At present, the positive electrode material of lithium iron phosphate battery plays a vital role in battery performance.

[0004] Existing lithium iron phosphate materials still have certain defects, such as poor low-temperature performance, which leads to low capacity retention rate of batteries prepared therefrom under low-temperature environment, limiting its application in certain extreme environments. Patent announcement number CN105293458B discloses a ferrous phosphate and its preparation method, a lithium ferrous phosphate positive electrode active material and its preparation method. The ferrous phosphate in this patent includes flaky particles, i.e., small particles distributed on the surface of the flaky particles; the particle size distribution of the flaky particles is 5-10 microns, and the particle size distribution of the small particles is 0.1-2 microns. The ion diffusion path in the small particle size material is also shortened accordingly, so that the diffusion rate of lithium ions during the charging and discharging process is increased, further improving the performance of the battery. However, the small particle size positive electrode active material prepared by this patent and the prior art still has the disadvantage of poor cycle performance. Summary of the invention

[0005] In order to solve the disadvantage that the small-particle cathode active material prepared by the prior art still has poor cycle performance, the purpose of the present invention is to provide a small-particle cathode active material, a preparation method and application thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a small-particle positive electrode active material comprises the following steps:

[0008] Step A1: ball-milling an iron-doped carbon source and nitrogen source composition, lithium hydroxide, and ammonium dihydrogen phosphate for 1-1.5 hours to obtain precursor particles, wherein the iron-doped carbon source and nitrogen source composition is prepared by complexing a gallic acid / melamine composition with ferric chloride hexahydrate;

[0009] Among them, the mass ratio of the iron-doped carbon source and nitrogen source composition, lithium hydroxide, and ammonium dihydrogen phosphate is 2.23g:0.24g:1.15g.

[0010] When iron forms a composition together with a carbon source and a nitrogen source, they can contact and mix more fully during the ball milling mixing process. This helps to ensure that the iron element is evenly distributed in the final positive electrode active material, avoiding local concentrations that are too high or too low. Evenly distributed iron ions can provide more active sites, which are conducive to the insertion and deinsertion of lithium ions, thereby improving the electrochemical performance of the battery, and the uniform mixing of carbon sources and nitrogen sources helps to form a uniform monodisperse morphology, thereby improving the electrochemical performance of the positive electrode active material, including the discharge specific capacity at different charge and discharge rates. The carbon source can limit the growth of lithium iron phosphate grains in the sintering furnace during the ball milling process, thereby helping to reduce the particle size.

[0011] The doping of carbon source and nitrogen source can also enhance the structural stability of lithium iron phosphate particles, prevent the particles from agglomerating or growing abnormally during the sintering process, and thus reduce the particle size of the particles.

[0012] Step A2: sintering the precursor particles in an inert atmosphere to obtain a positive electrode active material with a small particle size.

[0013] Furthermore, in step A2, the gas of the inert atmosphere is either nitrogen or argon.

[0014] Furthermore, in step A2, the sintering temperature is 650-800° C., and the sintering time is 1-2 h.

[0015] The iron-doped carbon source and nitrogen source composition contains carbon and nitrogen sources provided by the gallic acid / melamine composition. Gallic acid is an organic carbon source. The organic carbon source has a more significant effect on the electrochemical properties of the material. This is mainly because the organic carbon source undergoes thermal decomposition during the sintering process, and the decomposed carbon can be more tightly coated on the surface of the material, thereby improving the conductivity. Melamine is rich in nitrogen. The iron-doped carbon source and nitrogen source composition, which contains a N-containing carbon source, can form an in-situ N-doped carbon layer during the calcination process. N doping can introduce additional electrons or holes into the lattice of the carbon material, thereby changing its electronic structure. This change makes the N-doped carbon layer have a higher electron mobility, thereby improving the conductivity of the material, making the transmission of electrons in the positive electrode material smoother, thereby increasing the discharge capacity of the battery; the N-doped carbon layer reduces the energy barrier for ion penetration, making it easier for lithium ions to migrate during the battery cycle, thereby reducing the polarization phenomenon and capacity attenuation of the battery and extending the cycle life of the battery. Furthermore, the N-doped carbon layer can also serve as a protective layer to reduce the side reactions between the electrolyte and the positive electrode material, further extending the cycle life of the battery.

[0016] Most of the pores of the iron-doped carbon source and nitrogen source composition after sintering are of a mesoporous structure with a large specific surface area, which provides an electrical / ion transmission channel for the lithium ion storage process, accelerates the diffusion of the electrolyte, and improves the electrochemical performance of the battery.

[0017] The iron-doped carbon source and nitrogen source composition can provide a carbon skeleton with good mechanical strength, which not only improves the overall electrical conductivity but also facilitates the rapid diffusion of lithium ions in the porous structure, thereby improving the electrochemical performance of the battery.

[0018] Furthermore, the preparation method of the iron-doped carbon source and nitrogen source composition is as follows:

[0019] Step B1: adding gallic acid and melamine into deionized water, stirring at 80° C. for 1.5-2 hours, and then keeping at 180° C. for 12 hours, taking out, and drying at 80° C. to obtain a gallic acid / melamine composition;

[0020] Wherein, the mass ratio of gallic acid, melamine and deionized water is 5.1g:3.2g:80-100mL.

[0021] Step B2: Add the gallic acid / melamine composition and ferric chloride hexahydrate into deionized water, react at room temperature for 2-4 hours, and dry to obtain an iron-doped carbon source and nitrogen source composition.

[0022] The carboxyl group of gallic acid can react with the amino group of melamine to form an amide group, thereby forming a gallic acid / melamine composition. The gallic acid / melamine composition contains a large amount of phenolic hydroxyl groups, which can be complexed with iron ions to form an iron-doped carbon source and nitrogen source composition. The formation of the iron-doped carbon source and nitrogen source composition is conducive to the uniform combination of the three.

[0023] Wherein, the mass ratio of the gallic acid / melamine composition, ferric chloride hexahydrate and deionized water is 5g:1-1.2g:100-130mL.

[0024] Furthermore, a method for preparing a small-particle positive electrode active material and an application of a small-particle positive electrode active material prepared in a lithium-ion battery.

[0025] Beneficial effects of the present invention:

[0026] 1. The small-particle positive electrode active material prepared by the present invention has a small particle size and excellent electrochemical performance. The preparation method of the present invention is simple, which is conducive to large-scale production and has promotion and application value in the field of battery material technology. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Preparation Example 1

[0029] The preparation method of the iron-doped carbon source and nitrogen source composition of this preparation example is:

[0030] Step B1: 5.1 g of gallic acid and 3.2 g of melamine were added into 100 mL of deionized water, stirred at 80° C. for 1.5 h, and then kept at 180° C. for 12 h, taken out, and dried at 80° C. to obtain a gallic acid / melamine composition;

[0031] Step B2: Add 2.2 g of gallic acid / melamine composition and 0.27 g of ferric chloride hexahydrate into 100 mL of deionized water, react at room temperature for 2 h, and dry to obtain an iron-doped carbon source and nitrogen source composition.

[0032] Preparation Example 3

[0033] The preparation method of the iron-doped carbon source and nitrogen source composition of this preparation example is:

[0034] Step B1: 5.1 g of gallic acid and 3.2 g of melamine were added to 90 mL of deionized water, stirred at 80° C. for 1.7 h, and then kept at 180° C. for 12 h, taken out, and dried at 80° C. to obtain a gallic acid / melamine composition;

[0035] Step B2: Add 2.2 g of gallic acid / melamine composition and 0.27 g of ferric chloride hexahydrate into 120 mL of deionized water, react at room temperature for 3 h, and dry to obtain an iron-doped carbon source and nitrogen source composition.

[0036] Preparation Example 3

[0037] The preparation method of the iron-doped carbon source and nitrogen source composition of this preparation example is:

[0038] Step B1: 5.1 g of gallic acid and 3.2 g of melamine were added into 80 mL of deionized water, stirred at 80° C. for 2 h, and then kept at 180° C. for 12 h, taken out, and dried at 80° C. to obtain a gallic acid / melamine composition;

[0039] Step B2: Add 2.2 g of gallic acid / melamine composition and 0.27 g of ferric chloride hexahydrate into 130 mL of deionized water, react at room temperature for 4 h, and dry to obtain an iron-doped carbon source and nitrogen source composition.

[0040] Preparation Example 4

[0041] The preparation method of the iron-doped carbon source and nitrogen source composition of this preparation example is:

[0042] 2.2 g of gallic acid, 0.38 g of melamine, and 0.27 g of ferric chloride hexahydrate were added into 130 mL of deionized water, reacted at room temperature for 4 h, and dried to obtain an iron-doped carbon source and nitrogen source composition.

[0043] Preparation Example 5

[0044] The preparation method of the iron-doped carbon source composition of this preparation example is:

[0045] 2.2 g of gallic acid and 0.27 g of ferric chloride hexahydrate were added into 130 mL of deionized water, reacted at room temperature for 4 h, and dried to obtain an iron-doped carbon source and nitrogen source composition.

[0046] Example 1

[0047] This embodiment provides a method for preparing a small-particle positive electrode active material, comprising the following steps:

[0048] Step A1: 2.23 g of the iron-doped carbon source and nitrogen source composition prepared in Preparation Example 1, 0.24 g of lithium hydroxide, and 1.15 g of ammonium dihydrogen phosphate were ball-milled and mixed for 1 hour to obtain precursor particles;

[0049] Step A2: sintering the precursor particles in an inert nitrogen atmosphere at a sintering temperature of 650-800° C. for 1 h to obtain a positive electrode active material with a small particle size.

[0050] Example 2

[0051] This embodiment provides a method for preparing a small-particle positive electrode active material, comprising the following steps:

[0052] Step A1: 2.23 g of the iron-doped carbon source and nitrogen source composition prepared in Preparation Example 2, 0.24 g of lithium hydroxide, and 1.15 g of ammonium dihydrogen phosphate were ball-milled for 1.2 h to obtain precursor particles;

[0053] Step A2: sintering the precursor particles in an inert argon atmosphere at a sintering temperature of 700° C. for 2 h to obtain a positive electrode active material with a small particle size.

[0054] Example 3

[0055] This embodiment provides a method for preparing a small-particle positive electrode active material, comprising the following steps:

[0056] Step A1: 2.23 g of the iron-doped carbon source and nitrogen source composition prepared in Preparation Example 3, 0.24 g of lithium hydroxide, and 1.15 g of ammonium dihydrogen phosphate were ball-milled for 1.5 h to obtain precursor particles;

[0057] Step A2: sintering the precursor particles in an inert argon atmosphere at a sintering temperature of 800° C. for 1.5 h to obtain a positive electrode active material with a small particle size.

[0058] Comparative Example 1

[0059] A method for preparing a small-particle positive electrode active material. Compared with Example 1, the iron-doped carbon source and nitrogen source composition in Example 1 is replaced by the product prepared in Preparation Example 4, and the remaining raw materials and steps are the same as Example 1.

[0060] Comparative Example 2

[0061] A method for preparing a small-particle positive electrode active material. Compared with Example 1, the iron-doped carbon source and nitrogen source composition in Example 1 is replaced by the product prepared in Preparation Example 5, and the remaining raw materials and steps are the same as Example 1.

[0062] Comparative Example 3

[0063] This embodiment provides a method for preparing a small-particle positive electrode active material, comprising the following steps:

[0064] Step A1: 0.49 g of ferric chloride, 0.24 g of lithium hydroxide, and 1.15 g of ammonium dihydrogen phosphate were ball-milled for 1.5 h to obtain precursor particles;

[0065] Step A2: sintering the precursor particles in an inert argon atmosphere at a sintering temperature of 800° C. for 1.5 h to obtain a positive electrode active material with a small particle size.

[0066] The battery performance test of the small-particle positive electrode active materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 includes the following steps:

[0067] (1) Preparation of positive electrode sheets: The small-particle positive electrode active materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were dispersed in N-methylpyrrolidone with acetylene black and PVDF at a weight ratio of 90:5:5, respectively. The mixture was stirred evenly and coated on aluminum foil. The mixture was baked at a temperature of 100±5°C and rolled using a tablet press. The positive electrode sheets were cut into rolls. Each positive electrode sheet contained 10 g of positive electrode active material.

[0068] (2) Then, a button-type half-cell was assembled with a lithium sheet as the negative electrode, a polypropylene film as the separator, and 1.0 mol / L Li PF6 / (EC+EMC+DMC) (where the mass ratio of EC, EMC, and DMC was 1:1:1) as the electrolyte for electrochemical performance testing.

[0069] (3) Specific capacity test: The battery samples prepared above were placed at room temperature for 5 min, then charged at a constant current of 0.1 C with a cut-off voltage of 3.8 V, then charged at a constant voltage of 3.8 V with a cut-off current of 50 μA, placed for 5 min, and then discharged at a constant current of 0.1 C with a limit voltage of 2 V. The initial charge capacity and discharge capacity of the battery were recorded, and the mass specific capacity of the battery was calculated according to the following formula; mass specific charge capacity = battery initial charge capacity (mAh) / positive electrode material weight (g); mass specific discharge capacity = battery initial discharge capacity (mAh) / positive electrode material weight (g). The test results are shown in Table 1.

[0070] (4) Cycle performance test: The battery samples prepared above were charged at room temperature at a constant current of 1C, with a voltage limit of 3.8V, and then charged at a constant voltage of 3.8V, with a cut-off current of 50μA. The battery samples were left for 5 min and discharged at a constant current of 1C. The discharge capacity was recorded. The discharge capacity was recorded after repeating this process 500 times. The capacity retention rate after 500 times was calculated. The capacity retention rate = discharge capacity after 500 times (mAh) / first discharge capacity. The test results are shown in Table 1.

[0071] Table 1

[0072]

[0073]

[0074] It can be seen from Table 1 that the battery performance of Examples 1 to 3 is better than that of Comparative Examples 1 to 3. In Comparative Example 1, gallic acid and melamine do not react, and the dispersibility of the two as carbon sources and nitrogen sources is poor, so the electrochemical performance is reduced; Comparative Example 2 does not contain a nitrogen source, and the N carbon source can form an in-situ N-doped carbon layer during the calcination process. N doping can introduce additional electrons or holes in the lattice of the carbon material, thereby changing its electronic structure. This change makes the N-doped carbon layer have a higher electron mobility, thereby improving the conductivity of the material, making the transmission of electrons in the positive electrode material smoother, thereby improving the discharge capacity of the battery; the N-doped carbon layer reduces the energy barrier for ion penetration, making the migration of lithium ions easier during the battery cycle, thereby reducing the polarization phenomenon and capacity decay of the battery and extending the cycle life of the battery. Furthermore, the N-doped carbon layer can also serve as a protective layer to reduce the side reaction between the electrolyte and the positive electrode material, further extending the cycle life of the battery. This comparative example does not contain an N source, so the electrochemical performance is reduced; Comparative Example 3 does not contain a nitrogen source and a carbon source, and the iron ions are not a composition composed of a complex, and the electrochemical performance is the worst.

[0075] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a small-particle positive electrode active material, characterized in that: The following steps are involved: Step A1: ball-milling an iron-doped carbon source and nitrogen source composition, lithium hydroxide, and ammonium dihydrogen phosphate for 1-1.5 hours to obtain precursor particles, wherein the iron-doped carbon source and nitrogen source composition is prepared by complexing a gallic acid / melamine composition with ferric chloride hexahydrate; Step A2: sintering the precursor particles in an inert atmosphere to obtain a small-particle positive electrode active material.

2. The method for preparing a small-particle positive electrode active material according to claim 1, wherein: In step A1, the mass ratio of the iron-doped carbon source and nitrogen source composition, lithium hydroxide, and ammonium dihydrogen phosphate is 2.47 g:1.15 g:0.24 g.

3. The method for preparing a small-particle positive electrode active material according to claim 1, wherein: In step A2, the inert atmosphere gas is either nitrogen or argon.

4. The method for preparing a small-particle positive electrode active material according to claim 1, wherein: In step A2, the sintering temperature is 650-800° C., and the sintering time is 1-2 hours.

5. The method for preparing a small-particle positive electrode active material according to claim 1, wherein: The preparation method of the iron-doped carbon source and nitrogen source composition is as follows: Step B1: adding gallic acid and melamine to deionized water, stirring at 80° C. for 1.5-2 hours, then keeping the mixture at 180° C. for 12 hours, removing the mixture, and drying the mixture at 80° C. to obtain a gallic acid / melamine composition; Step B2: Add the gallic acid / melamine composition and ferric chloride hexahydrate into deionized water, react at room temperature for 2-4 hours, and dry to obtain an iron-doped carbon source and nitrogen source composition.

6. The method for preparing a small-particle positive electrode active material according to claim 5, characterized in that: In step B1, the mass ratio of gallic acid, melamine and deionized water is 5.1 g:3.2 g:80-100 mL.

7. The method for preparing a small-particle positive electrode active material according to claim 5, characterized in that: In step B2, the mass ratio of the gallic acid / melamine composition, ferric chloride hexahydrate, and deionized water is 2.2 g:0.27 g:100-130 mL.

8. A small-particle positive electrode active material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

9. Use of the small-particle positive electrode active material according to claim 8 in a lithium-ion battery.

Citation Information

Patent Citations

  • Ferrous phosphate and its preparation method, lithium iron phosphate cathode active material and its preparation method

    CN105293458B